Summer coworking as an element of a comfortable urban environment - Bareicheva M.A.; Kubina E.A.; Stepanova N.R. (E3S Web of Conferences, 2024)
The paper deals with the problems of improvement and the creation of a comfortable urban environment. An initiative youth project is an idea of creating a summer coworking on the territory of the Ural Federal University in Ekaterinburg. Here, the University can take responsibility for designing the urban environment and involving urban communities in the development of the city. The article presents the concept of creating a creative open space for work and leisure that will unite citizens, as well as raise the issue of using collaborative design in creating a comfortable urban environment. The author’s developments in creating a unique social object-a summer coworking – are presented. Based on real urban practices and the role of the University as a driver of regional development, the authors of the project plan to create a place for open and trusting inter-social communication between representatives of government, business, public associations, and active citizens. The possibilities of points of growth and development of the formed space were also considered. The implementation of the presented project will improve and improve the territory of the city of Ekaterinburg.